The Influence Of Financial Literacy, Financial Behavior, And Hedonistic Lifestyle On Financial Management University Students In Lubuklinggau City - Rimbano, Dheo; Famalika, Ade; Sari, Wisdalia Maya; Sari, Tri Agriana; Widyana, Widyana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to examine the influence of financial literacy, financial behavior, and hedonistic lifestyle on the financial management of students in Lubuklinggau City. This research adopts a quantitative approach using Structural Equation Modeling (SEM) with the SmartPLS application to analyze the relationships among variables. Data were collected from 100 high school students through a stratified random sampling technique to ensure representative results. The findings reveal that financial literacy has a positive and significant effect on financial behavior and financial management, indicating that students with higher financial knowledge tend to manage their finances more effectively. Furthermore, financial behavior also shows a positive and significant influence on financial management, suggesting that good habits such as budgeting, saving, and controlling expenses contribute to better financial outcomes among students. However, the hedonistic lifestyle variable does not show a significant impact on financial behavior or financial management. This indicates that although students may engage in modern or pleasure-oriented lifestyles, such tendencies do not necessarily determine their ability to manage finances. In general, student financial management is more strongly influenced by financial literacy and long-term financial awareness than by hedonistic lifestyle factors. These results highlight the crucial role of financial education in shaping responsible financial behavior and promoting sustainable financial management practices. Therefore, improving financial literacy and strengthening students’ understanding of financial planning are essential strategies to encourage efficient and sustainable financial management among young generations.